2015
DOI: 10.1080/17470218.2015.1023206
|View full text |Cite
|
Sign up to set email alerts
|

Inclined to see it your way: Do altercentric intrusion effects in visual perspective taking reflect an intrinsically social process?

Abstract: It has been suggested that some aspects of mental state understanding recruit a rudimentary, but fast and efficient, processing system, demonstrated by the obligatory slowing down of judgements about what the self can see when this is incongruent with what another can see. We tested the social nature of this system by investigating to what extent these altercentric intrusions are elicited under conditions that differed in their social relevance and, further, how these related to self-reported social perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
89
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(104 citation statements)
references
References 66 publications
(115 reference statements)
12
89
3
Order By: Relevance
“…each saw a different number of discs), while in others they were consistent. To examine the influence of perspective switching, the order of trials was pseudorandomised such that half the trials were preceded by a trial with the same perspective cue Behavioural results largely replicated previous studies of this kind Surtees & Apperly, 2012;Qureshi et al, 2010;Nielsen et al, 2015), showing higher accuracy and faster response times when participants shared the same visual perspective as the on-screen avatar, compared to when the two perspectives were different. However in our study the reduced accuracy on inconsistent versus consistent trials was only significant when participants were prompted to take the avatarÕs perspective, and not when taking the self perspective.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…each saw a different number of discs), while in others they were consistent. To examine the influence of perspective switching, the order of trials was pseudorandomised such that half the trials were preceded by a trial with the same perspective cue Behavioural results largely replicated previous studies of this kind Surtees & Apperly, 2012;Qureshi et al, 2010;Nielsen et al, 2015), showing higher accuracy and faster response times when participants shared the same visual perspective as the on-screen avatar, compared to when the two perspectives were different. However in our study the reduced accuracy on inconsistent versus consistent trials was only significant when participants were prompted to take the avatarÕs perspective, and not when taking the self perspective.…”
Section: Discussionsupporting
confidence: 62%
“…Crucially, this methodology should also provide a means of disentangling traditional mentalising accounts for spontaneous visual 7 perspective-taking from directional (or sub-mentalising) accounts, which suggest that attention is driven by domain-general processes based on directional features of the avatar (Heyes, 2014;Santiesteban, Catmur, Hopkins, Bird, & Heyes, 2014). Specifically, Santiesteban et al (2014) found a comparable reaction time difference between consistent and inconsistent trials when the central avatar was replaced with an arrow (but see Schurz, Kronbichler, Weissengruber, Surtees, Samson, &Perner, 2015 andNielsen et al, 2015). Since arrows provide directional, but not agentive, cues the authors interpret this as evidence against an implicit mentalising account of the altercentric effect, and instead supports the role of attentional processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that we do not argue that the dot perspective task does not involve any social processing mechanisms, only those concerned with spontaneous perspective taking. This is based on recent evidence by Nielsen, Slade, Levy, and Holmes (2015) who showed that the degree of spontaneous perspective taking positively correlates with self-reported empathy. Finally, future workers may want to consider employing the occluding barrier technique when using other paradigms suggestive of spontaneous perspective taking.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a body of research has emerged on social perspective-taking, which argues that taking a perspective is an intrinsically social process that relates to Theory of Mind (Samson, Apperly, Braithwaite, Andrews, & Bodley Scott, 2010;Nielsen et al, 2015). It has also been suggested that when evaluating their own perspective, people are affected by the perspective of other individuals (Samson et al, 2010).…”
Section: Egocentric and Allocentric Biasesmentioning
confidence: 99%